First report of cycas necrotic stunt virus in a hybrid peony in South Korea - Ju-Yeon Yoon; Chandara Soeng; Ho-Jong Ju; In-Sook Cho; Bong Nam Chung (Journal of Plant Pathology, 2024)

First report on natural infection of Nepenthes alata by pepper mild mottle virus in Korea - Ga-Eun Lee; Hae-Jun Kim; In-Sook Cho; Rae-Dong Jeong (Journal of Plant Pathology, 2023)

First report of tomato spotted wilt virus infecting lobelia in South Korea - In-Sook Cho; Bong-Nam Chung; Seung-Kook Choi; Sena Choi; John Hammond; Hyoun-Sub Lim (Journal of Plant Pathology, 2023)

First report of natural infection of Malva vertillata by turnip mosaic virus in Korea - Hyo-Jeong Lee; In-Sook Cho; Rae-Dong Jeong (Journal of Plant Pathology, 2023)

Development and application of a reverse transcription droplet digital PCR assay for detection and quantification of Plantago asiatica mosaic virus - Hyo-Jeong Lee; Sena Choi; In-Sook Cho; Ju-Yeon Yoon; Rae-Dong Jeong (Crop Protection, 2023)

Regulation of mast cell activation by extracellular vesicles in cow’s milk casein-induced allergic responses - Young-Eun Cho; Hyun-Woo Kim; Keun Young Min; Jin-Hyeon Hwang; Dong-Ha Kim; Jee-In Kim; Guo Nan Yin; Jae-Hwan Lim; In-Sook Kwun; Moon-Chang Baek; Do-Kyun Kim (Molecular & Cellular Toxicology, 2022)

Construction of full-length infectious clones of turnip mosaic virus isolates infecting Perilla frutescens and genetic analysis of recently emerged strains in Korea - Zheng-Xing Song; Su-Jeong Chu; Eun-Young Seo; Wen-Xing Hu; Yong Pyo Lim; Tae-Seon Park; Ji-Soo Park; Jin-Sung Hong; In-Sook Cho; John Hammond; Hyoun-Sub Lim (Archives of Virology, 2022)

Construction of full-length infectious cDNA clones of two Korean isolates of turnip mosaic virus breaking resistance in Brassica napus - Zheng-Xing Song; Eun-Young Seo; Wen-Xing Hu; Jong-Hyeon Jeong; Jae Sun Moon; Kang-Hee Kim; Won-Seob Eom; In-Sook Cho; John Hammond; Hyoun-Sub Lim (Archives of Virology, 2022)

Anti-inflammatory activity of palmitoylethanolamide ameliorates osteoarthritis induced by monosodium iodoacetate in Sprague–Dawley rats - Jae In Jung; Hyun Sook Lee; Young Eun Jeon; So Mi Kim; Su Hee Hong; Joo Myung Moon; Cho Young Lim; Yoon Hee Kim; Eun Ji Kim (Inflammopharmacology, 2021)
Novel treatment strategies are urgently required for osteoarthritis (OA). Palmitoylethanolamide (PEA) is a naturally occurring fatty acid amide with analgesic and anti-inflammatory effects. We aimed to examine its effect on OA and elucidate the molecular mechanism of actions in monosodium iodoacetate (MIA)-induced OA Sprague–Dawley rats. The experimental animals were divided into normal control group (injected with saline + treated with phosphate-buffered saline (PBS), NOR), control group (injected with MIA + treated with PBS, CON), 50 or 100 mg/kg body weight (BW)/day PEA-treated group (injected with MIA + treated with 50 or 100 mg of PEA/kg BW/day, PEA50 or PEA100), and positive control group (injected with MIA + treated with 6 mg of diclofenac/kg BW/day, DiC). The changes in blood parameters, body parameters, gene expression of inflammatory mediators and cytokines, knee thickness, and joint tissue were observed. Oral administration of PEA had no adverse effects on the BW, liver, or kidneys. PEA reduced knee joint swelling and cartilage degradation in MIA-induced OA rats. The serum levels of leukotriene B4, nitric oxide, tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and prostaglandin E2 considerably reduced in the PEA100 group compared with those in the CON group. In the synovia of knee joints, the mRNA expression of iNOS , 5-Lox , Cox-2 , Il-1β , Tnf-α , and Mmp-2 , -3 , -9 , and -13 apparently increased with MIA administration. Meanwhile, Timp-1 mRNA expression apparently decreased in the CON group but increased to the normal level with PEA treatment. Thus, PEA can be an effective therapeutic agent for OA.

First report of tomato mosaic virus infecting chili pepper (Capsicum annuum L.) in Korea - In-Sook Cho; Ju-Yeon Yoon; Eun-Young Yang; Soo-Young Chae; Bong Nam Chung; John Hammond; Hyoun Sub Lim (Journal of Plant Pathology, 2021)

Changes in the chemical properties of coir dust with increasing aging time and development of a method for determining moderate aging degree - Yun Seob Kim; In Sook Park; Eunsoo Park; Byoung-Kwan Cho; Chiwon W. Lee; Jong Myung Choi (Horticulture, Environment, and Biotechnology, 2021)

Rapid detection of plum pox virus by reverse transcription recombinase polymerase amplification - Hwi-Won Jeong; Hyo-Jeong Lee; In-Sook Cho; Ho-Jong Ju; Rae-Dong Jeong (Journal of Plant Diseases and Protection, 2021)

First report of tomato spotted wilt virus infecting Cirsium setidens in Korea - Seongmu Mun; Su-Yeon Hwang; Na-Kyeong Kim; In-Sook Cho; Ho-Jong Ju; Rae-Dong Jeong (Journal of Plant Pathology, 2021)

First report of cucumber green mottle mosaic virus infecting Perilla frutescens in Korea and the world - In-Sook Cho; Ju-Yeon Yoon; Bong-Nam Chung; Hyoun-Sub Lim (Journal of Plant Pathology, 2021)

Implantable electrical stimulation bioreactor with liquid crystal polymer-based electrodes for enhanced bone regeneration at mandibular large defects in rabbit - Chaebin Kim; Hoon Joo Yang; Tae Hyung Cho; Beom Seok Lee; Tae Mok Gwon; Soowon Shin; In Sook Kim; Sung June Kim; Soon Jung Hwang (Medical & Biological Engineering & Computing, 2020)

Length of poly(A) tail affects transcript infectivity of three ZYMV symptom variants differing at only five amino acid positions - Boram Kim; In-Sook Cho; Ik-Hyun Kim; Go-Woon Choi; Hye-Kyoung Ju; Wen-Xing Hu; June-Pyo Oh; Jung-Kyu Kim; Eunyong Seo; Leslie L. Domier; John Hammond; Hyoun-Sub Lim (Journal of Plant Pathology, 2019)

First report of zucchini yellow mosaic virus in muskmelon (Cucumis melo) in Korea - In-Sook Cho; Bong-Nam Chung; Sun-Jung Kwon; Ju-Yeon Yoon; Gug-Seoun Choi; Boram Kim; John Hammond; Hyoun-Sub Lim (Journal of Plant Pathology, 2019)

Amino acid differences in the N-terminal half of the polyprotein of Chinese turnip mosaic virus isolates affect symptom expression in Nicotiana benthamiana and radish - Wen-Xing Hu; Eun-Young Seo; In-Sook Cho; Jung-Kyu Kim; Hye-Kyoung Ju; Ik-Hyun Kim; Go-Woon Choi; Boram Kim; Chun-Hee Ahn; Leslie L. Domier; Sang-Keun Oh; John Hammond; et al. (Archives of Virology, 2019)

Identification of rehmannia virus 1, a novel putative member of the genus Closterovirus, from Rehmannia glutinosa - Sun-Jung Kwon; Meilan Jin; In-Sook Cho; Ju-Yeon Yoon; Gug-Seoun Choi (Archives of Virology, 2018)

Complete nucleotide sequence of a highly divergent cherry-associated luteovirus (ChALV) isolate from peach in South Korea - Davaajargal Igori; Seungmo Lim; Dasom Baek; In Sook Cho; Jae Sun Moon (Archives of Virology, 2017)

First report of cherry virus A infecting Prunus mume in South Korea - Seungmo Lim; Davaajargal Igori; Dasom Baek; In-Sook Cho; Gug-Seoun Choi; Jae Sun Moon (VirusDisease, 2017)

Complete nucleotide sequence and genome organization of peach virus D, a putative new member of the genus Marafivirus - Davaajargal Igori; Seungmo Lim; Dasom Baek; San Yeong Kim; Euncheol Seo; In-Sook Cho; Gug-Seoun Choi; Hyoun-Sub Lim; Jae Sun Moon (Archives of Virology, 2017)

Molecular detection and characterization of a divergent isolate of Plantago asiatica mosaic virus in Plantago asiatica - Seungmo Lim; Davaajargal Igori; Fumei Zhao; Yun Su Do; In-Sook Cho; Gug-Seoun Choi; Jae Sun Moon (VirusDisease, 2016)

Comparative study of BMP-2 alone and combined with VEGF carried by hydrogel for maxillary alveolar bone regeneration - Sook Kyoung Kim; Tae Hyung Cho; Jeong Joon Han; In Sook Kim; Yongdoo Park; Soon Jung Hwang (Tissue Engineering and Regenerative Medicine, 2016)

Genomic detection and characterization of a Korean isolate of Little cherry virus 1 sampled from a peach tree - Seungmo Lim; Davaajargal Igori; Ran Hee Yoo; Fumei Zhao; In-Sook Cho; Gug-Seoun Choi; Hyoun-Sub Lim; Su-Heon Lee; Jae Sun Moon (Virus Genes, 2015)

Enhanced regeneration of rabbit mandibular defects through a combined treatment of electrical stimulation and rhBMP-2 application - Junghoon Kim; Hoon Joo Yang; Tae Hyung Cho; Sung Eun Lee; Yong Doo Park; Hyun Man Kim; In Sook Kim; Young-kwon Seo; Soon Jung Hwang; Sung June Kim (Medical & Biological Engineering & Computing, 2013)

A rice dehydration-inducible SNF1-related protein kinase 2 phosphorylates an abscisic acid responsive element-binding factor and associates with ABA signaling - Min-Ju Chae; Jung-Sook Lee; Myung-Hee Nam; Kun Cho; Ji-Yeon Hong; Sang-A Yi; Seok-Cheol Suh; In-Sun Yoon (Plant Molecular Biology, 2006)

In vivo MR Imaging of Tissue-engineered Human Mesenchymal Stem Cells Transplanted to Mouse: a Preliminary Study - In Kap Ko; Ho-Taek Song; Eun-Jin Cho; Eun Sook Lee; Yong-Min Huh; Jin-Suck Suh (Annals of Biomedical Engineering, 2006)

Isolation and characterization ofPanax ginseng 14-3-3 gene family - Hwa -Jee Chung; Joo Young Park; In Sook Cho; Cheol Goo Hur; Dong -Woog Choi; Jang Ryol Liu (Journal of Plant Biology, 2004)

Changes in gene expression during hairy root formation byAgrobacterium rhizogenes infection in ginseng - Hwa -Jee Chung; In Sook Cho; Jee -Hyub Kim; Dong Su In; Cheol Goo Hur; Ji Sook Song; Sung Sick Woo; Dong -Woog Choi; Jang Ryol Liu (Journal of Plant Biology, 2003)

A new class II rice chitinase, Rcht2, whose induction by fungal elicitor is abolished by protein phosphatase 1 and 2A inhibitor - Cha Young Kim; Sang Wan Gal; Mi Sook Choe; Sun Yong Jeong; Soo In Lee; Yong Hwa Cheong; Sang Hyoung Lee; Young Ju Choi; Chang-deok Han; Kyu Young Kang; Moo Je Cho (Plant Molecular Biology, 1998)